Spatial Specialization and Farm-Nonfarm Linkages - Deichmann, Uwe; Shilpi, Forhad; Vakis, Renos (World Bank, Washington, DC, 2012)
Using individual level employment data from Bangladesh, this paper presents empirical evidence on the relative importance of farm and urban linkages for rural nonfarm employment. The econometric results indicate that high return wage work and self-employment in nonfarm activities cluster around major urban centers. The negative effects of isolation on high return wage work and on self-employment are magnified in locations with higher agricultural potential. The low return nonfarm activities respond primarily to local demand displaying no significant spatial variation. The empirical results highlight the need for improved connectivity of regions with higher agricultural potential to urban centers for nonfarm development in Bangladesh.